2014
DOI: 10.2478/s13533-012-0148-1
|View full text |Cite
|
Sign up to set email alerts
|

Filling in missing sea-surface temperature satellite data over the Eastern Mediterranean Sea using the DINEOF algorithm

Abstract: The Data Interpolating Empirical Orthogonal Functions method is a special technique based on EmpiricalOrthogonal Functions and developed to reconstruct missing data from satellite images, which is especially useful for filling in missing data from geophysical fields. Successful experiments in the Western Mediterranean encouraged extension of the application eastwards using a similar experimental implementation. The present study summarizes the experimental work done, the implementation of the method and its ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Another approach for analyzing a set of satellite images (data interpolating empirical orthogonal functions -DINEOF) uses the data to create a truncated empirical orthogonal function (EOF) representation of the data set to fill in missing data (e.g., Beckers and Rixen, 2003;AlveraAzcárate et al, 2005AlveraAzcárate et al, , 2007. The latter method has been favorably compared to OI and has been exploited in a series of applications (e.g., Sheng et al, 2009;Ganzedo et al, 2011;Nikolaidis et al, 2014;Wang and Liu, 2014), including operational setups (e.g., Volpe et al, 2012). In some situations, however, the truncation of the EOFs series can reject some interesting small-scale features that only give a small contribution to the total variance, and that can often be split into several modes (Sirjacobs et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Another approach for analyzing a set of satellite images (data interpolating empirical orthogonal functions -DINEOF) uses the data to create a truncated empirical orthogonal function (EOF) representation of the data set to fill in missing data (e.g., Beckers and Rixen, 2003;AlveraAzcárate et al, 2005AlveraAzcárate et al, , 2007. The latter method has been favorably compared to OI and has been exploited in a series of applications (e.g., Sheng et al, 2009;Ganzedo et al, 2011;Nikolaidis et al, 2014;Wang and Liu, 2014), including operational setups (e.g., Volpe et al, 2012). In some situations, however, the truncation of the EOFs series can reject some interesting small-scale features that only give a small contribution to the total variance, and that can often be split into several modes (Sirjacobs et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In [24], the authors deal with wave data and the data filling takes place in three-hour intervals. In [25], the method is used for recovering images from a satellite; however, no evaluation metrics are used for the method's performance.…”
Section: Motivation and State-of-the-artmentioning
confidence: 99%
“…The Southern Ocean Carbon and Climate Observations and Modeling (SOCCOM) program recently reported that 31 profiling floats carrying nitrate sensors have successfully transmitted 40 complete nitrate annual cycles (Johnson et al 2017), and additional float deployments are being carried out. Multiple methods and techniques have been developed to reconstruct fields in regions with sparse observational data, such as optimal interpolation (Reynolds and Smith 1994;Schneider 2001), model-based gapfilling techniques (e.g., data assimilation; Stammer et al 2002;Wunsch and Heimbach 2007;Mazloff et al 2010;Verdy and Mazloff 2017), and empirical orthogonal function (EOF)-based methods (e.g., Smith et al 1996;Kaplan et al 1997;Beckers and Rixen 2003;Alvera-Azcárate et al 2005;Kondrashov and Ghil 2006;Alvera-Azcárate et al 2007;Alvera-Azcárate et al 2011;Nikolaidis et al 2014;Alvera-Azcárate et al 2016). The EOF-based methods, in particular, show advantages over the other methods in terms of ease of implementation and accuracy relative to computational costs (Alvera-Azcárate et al 2005).…”
Section: Introductionmentioning
confidence: 99%